YouTube viewers in diapers: An exploration of factors associated with amount of toddlers’ online viewing - Nelly Elias; Idit Sulkin (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2017)
Recent studies show that television is no longer the primary choice for screen viewing among very young children, having been surpassed by online viewing platforms, among which YouTube is dominant. YouTube’s simple user interface, that allows even toddlers to proceed to the next item on the playlist and affords them easy access to their favorite videos, has been suggested as the key to its popularity with very young audiences. On the other hand, young children’s lack of technical, critical and social skills renders them particularly vulnerable to commercial and age-inappropriate content that they might encounter online. In this rapidly changing media environment, in which more and more children begin online activity at a much younger age, it is crucial to evaluate the amount of young children’s online viewing and the factors that determine their viewing habits. Consequently, the present study aimed at identifying the profile of toddler online viewers based on child, parent and family-related characteristics and revealing predictors that might explain higher online exposure. The study, based on a face-to-face survey conducted in Israel among 289 parents of toddlers aged 18-36 months, reveals that online viewing has become normative behavior among toddlers and emphasizes how deeply online viewing is integrated into the basic daily routine of parents with very young children who use online viewing platforms to fulfill a wide range of their childrearing needs.